AKTIVITAS ANTIBAKTERI DAN UJI KARAKTERISTIK FISIK CLAY MASK EKSTRAK BUAH PARIJOTO (Medinilla speciosa Blume) Terhadap Bakteri Staphylococcus aureus - Alya Narulita; Muhammad Nurul Fadel; Emma Jayanti Besan (Yayasan Nusantara Hasana Berdikari, 2025)
Natural ingredients are used as an alternative to the use of synthetic drugs and antibiotics, due to the small side effects caused compared to synthetic drugs. Parijoto fruit (Medinilla speciosa Blume) has many benefits, one of which is as an acne-causing antibacterial with the content of flavonoid compounds, tannins, and saponins. The use of natural ingredients of parijoto fruit in the form of clay mask preparations was chosen because it has advantages and is popular among teenagers compared to other types of masks. This study aims to determine the effectiveness of clay mask preparation with 70% ethanol extract of parijoto fruit in inhibiting the activity of Staphylococus aaureus bacteria using the disc diffusion method. Parijoto fruit is extracted using the maceration method with 70% ethanol solvent to obtain a thick extract, then physical characteristics tests and antibacterial tests are carried out on clay mask preparations. Antibacterial testing of parijoto fruit extract used disc diffusion method with concentrations of 10%, 15%, and 20%. The results of the study showed that 70% ethanol extract clay mask preparations of parijoto fruit had moderate to strong antibacterial effectiveness against S. aureus in formulas F1 (10%), F2 (15%), and F3 (20%) with consecutive inhibition zones of 6.3 mm, 14.1 mm, 15.3 mm. The concentration of F3 (20%) showed the most optimal activity in inhibiting acne-causing S.aureus bacteria.